Strategi Pengembangan Kurikulum Berbasis Kompetensi Di Sekolah Dasar Inpres 16 Ende - Kotten, Natsir B (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2023)
This article aims to provide an overview of competency-based curriculum development strategies. Participants in this research are educators, school principals, parents, who have relevant experience and knowledge related to the Competency Based Curriculum. Data collection techniques use interviews, observation and documentation studies. Data analysis was carried out using a thematic approach. Research findings show: the Competency Based Curriculum development strategy is realized with an approach that emphasizes developing practical skills and applying knowledge to face the challenges of daily life, as well as creating a collaborative and inclusive educational environment with teachers, parents and students. The implications of the results of this research can be used by education policy makers to create strategies for developing a Competency Based Curriculum.